Clinical effectiveness of sodium bicarbonate therapy on mortality for septic patients with acute moderate lactic acidosis - Huang, Sai; Yang, Bo; Peng, Yaojun; Xing, Qinrui; Wang, Lili; Wang, Jing; Zhou, Xuan; Yao, Yuan; Chen, Li; Feng, Cong (Frontiers in Pharmacology, 2023)
Abstract Objective: This study aimed to explore the effectiveness of sodium bicarbonate (SB) administration on mortality in septic patients with acute moderate lactic acidosis (MLA). Methods: The large ICU database (MIMIC-IV) was retrospectively analyzed. Patients with sepsis and acute MLA were identified. Propensity score analysis (PSA) was performed to explain baseline differences in the probability of accepting or not accepting SB. The edge structured cox model (MSCM) was used to adjust for baseline and time-varying confounding variables. The primary outcome was the ICU and hospital mortality. The subgroup of septic shock was also investigated. Results: A total of 512 septic patients with acute MLA were identified in this study, including 160 in the SB group and 352 in the non-SB group. In the PSA, SB administration was associated with reduced ICU (HR 0.58, 95% CI 0.38–0.89; p <0.05) and hospital (HR 0.67, 95% CI 0.47–0.95; p <0.05) mortality in septic patients with acute MLA. In the subgroup, the results were similar with septic patients. In the MSCM, SB administration could also improve the ICU (HR 0.35, 95% CI 0.16–0.75; p <0.01) and (HR 0.50, 95% CI 0.28–0.88; p <0.05) mortality on septic patients. However, In the subgroup, SB administration could only be found associated with improved hospital (HR 0.44, 95% CI 0.20–0.97; p <0.05) survival in septic shock. Conclusion: SB administration treatment could reduce ICU and hospital mortality of septic patients with acute MLA. Meanwhile, it could also improve hospital survival in the subgroup of septic shock patients with acute MLA.